Doctoral Dissertation Writing: A Systematic Review of Challenges, Characteristics, and Scholarly Processes - DARDOUR , Majid (International Journal of Language and Literary Studies, 2025)
Completing a doctoral dissertation is a landmark achievement in a researcher's life, signifying the capability for independent thinking, extensive research, and contributory work in a desired academic area. Writing a dissertation is one of the most arduous periods of doctoral education, but it holds immense value. It represents a complex interplay of intellectual, technical, and affective requirements. This systematic review is grounded in a wide range of literature from academia to explore the major challenges faced by doctoral students, including choosing a research topic, selecting appropriate methodologies, effective time management, overcoming writing blocks, and psychological distress. Furthermore, the review outlines the key characteristics of a successful dissertation, including originality, methodological rigor, analytical thinking, and scholarly writing. Each stage of the dissertation journey is examined, ranging from initial planning and literature review to data analysis and preparation for defence, offering an interactive guide for doctoral students. Findings indicate that the timely completion of the dissertation is highly associated with institutional support, the quality of supervision, the availability of research training, and compliance with academic requirements. By synthesising key findings, this review aims to enhance the clarity and confidence of doctoral students and programs in navigating the dissertation process.